1999
DOI: 10.1259/bjr.72.858.10560332
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 18F-FDG positron emission tomography in gastric and oesophageal carcinoma.

Abstract: The aim of this study was to evaluate 18F-fluoro-deoxyglucose (FDG) positron emission tomography (PET) in gastric and oesophageal carcinoma. 16 patients with biopsy proven oesophageal or gastric carcinoma had PET scans. Four patients had advanced disease and received palliative treatment. The remaining 12 patients were randomized to immediate surgery or neoadjuvant chemotherapy. Three patients had repeat PET scans following chemotherapy. PET detected the primary tumour in all cases including stage T1 lesions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 10 publications
5
32
1
1
Order By: Relevance
“…The sensitivities of CT and FDG-PET for the detection of regional lymph node metastases were lower. It is already known that lymph nodes adjacent to the primary oesophageal cancer are difficult to discriminate from the primary tumour with FDG-PET (McAteer et al, 1999), which is due to the intense activity in the primary cancer and the limited spatial resolution of PET (Luketich et al, 1997;Rankin et al, 1998). Low sensitivity of CT for regional lymph node can at least partly be explained by the fact that CT is not able to detect metastases in normal-sized lymph nodes (Choi et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivities of CT and FDG-PET for the detection of regional lymph node metastases were lower. It is already known that lymph nodes adjacent to the primary oesophageal cancer are difficult to discriminate from the primary tumour with FDG-PET (McAteer et al, 1999), which is due to the intense activity in the primary cancer and the limited spatial resolution of PET (Luketich et al, 1997;Rankin et al, 1998). Low sensitivity of CT for regional lymph node can at least partly be explained by the fact that CT is not able to detect metastases in normal-sized lymph nodes (Choi et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that in all esophageal cancer patients, abnormal FDG accumulation is detected in primary tumors, with the average detection rate exceeding 90% (15,(20)(21)(22)(23). However, as the spatial resolution of PET or PET-CT is poor, it is limited in its ability to detect small tumors; in addition, the adjacent invasion of a primary tumor is difficult to assess in most cases (7,14).…”
Section: Discussionmentioning
confidence: 99%
“…Primary tumor detection has been reported in 69 -100% of patients with esophageal carcinoma. Some studies have reported that all patients with esophageal carcinoma had abnormal FDG accumulation in the primary tumor 8,10,13,32 ; the average detection rate in those reports was ÏŸ 90%. Himeno et al 35 reported that PET imaging could detect primary esophageal tumors with an invasion status of T1b or greater (i.e., tumors involving the submucosa), whereas T1a tumors (i.e., tumors invading the muscularis mucosae) were undetectable.…”
Section: Discussionmentioning
confidence: 99%